Aromatherapy Massage of Lemongrass, Kaffir Lime, and Lemon to Increase Appetite, IGF-1 (Insulin-like Growth Factor 1) Levels, Body Weight, and Height In Stunted Toddler - Yuliatri, Risa; Widyawati, Melyana Nurul; Suwondo, Ari; Walin, Walin (Green Publisher Indonesia, 2023)
Stunting is a chronic nutritional problem caused by malnutrition over a long period of time, resulting in children becoming short. Stunting is not only a problem of impaired physical growth, but also causes children to become easily sick, impaired brain development and intelligence, so stunting is a major threat to the quality of human resources in Indonesia. Indonesia's stunting prevalence is 24.4% in 2021, based on the results of the Indonesian Nutritional Status Survey (SSGI) by the Ministry of Health. This figure is quite high and still above the standard tolerated by WHO, which is below 20%. For this reason, efforts are needed to reduce stunting rates with aromatherapy footing. The study aims to analyze the effect of aromatherapy massage on appetite, IGF-1 levels, body weight, and height in stunted toddlers. The research design used was pretest-postest with control group design. The number of samples in this study was 32 subjects, which were divided into two groups, 16 subjects in the intervention group were given aromatherapy massage 3 times a week with a duration of 15 minutes for 8 weeks and the control group was given standard care for stunting toddlers given PMT biscuits. The probability sampling technique is simple random sampling. The data studied were appetite, IGF-1 levels, body weight, and height of stunted toddlers. Data analysis using Wilcoxon Test, Man Wihtney Test, Paired T-test, and Independent T-test. The results show there were differences between before and after aromatherapy massage in the intervention group on appetite (P = 0.001), IGF-1 levels (P = 0.000), body weight (P = 0.000), and height (P = 0.000). Aromatherapy massage 3 times a week for a duration of 15 minutes for 8 weeks is effective in increasing appetite, IGF-1 levels, weight, and height of stunted toddlers.